The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.heliyon.2020.e04212
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of staple crops by heavy metals in Sibaté, Colombia

Abstract: In the present study concentration of heavy metals [HMs], such as Cu, As, Pb, Cr, Zn, Co, Cd and Ni, present in vegetables included in the typical Colombian diet were measured. The study was conducted as follows: samples of parsley, artichoke and carrots produced in a location near the Muña dam were collected, where the Bogot a River water is treated for use as a water resource. To determine food safety, national and international [HMs] established limits were compared with quantified [HMs] in samples of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
(25 reference statements)
0
8
0
2
Order By: Relevance
“…Los datos evaluados presentan alta variabilidad, evidenciado por el alto valor del coeficiente de variación (> 18%), siendo el más bajo, para las muestras de hoja en Nueve de Julio (< 18%) (Tabla 1). Estos resultados son diferentes a lo reportado por Karimi et al (2019), quienes, en un ensayo hidropónico, observaron mayor acumulación de Cd en tallos de Cynara scolymus L. Asimismo, los datos de esta evaluación, son superiores a los reportados por Lizarazo et al (2020) y Machado (2016), indicando una alta traslocación del Cd absorbido hacia las hojas, y alta contaminación del cultivo de alcachofa en los distritos de Nueve de Julio y Mito. En Mito se observó mayor concentración de Cd en hojas, tallos y frutos de Cynara scolymus L. en el distrito Nueve de Julio (Tabla 2).…”
Section: Concentración De Cadmiounclassified
See 1 more Smart Citation
“…Los datos evaluados presentan alta variabilidad, evidenciado por el alto valor del coeficiente de variación (> 18%), siendo el más bajo, para las muestras de hoja en Nueve de Julio (< 18%) (Tabla 1). Estos resultados son diferentes a lo reportado por Karimi et al (2019), quienes, en un ensayo hidropónico, observaron mayor acumulación de Cd en tallos de Cynara scolymus L. Asimismo, los datos de esta evaluación, son superiores a los reportados por Lizarazo et al (2020) y Machado (2016), indicando una alta traslocación del Cd absorbido hacia las hojas, y alta contaminación del cultivo de alcachofa en los distritos de Nueve de Julio y Mito. En Mito se observó mayor concentración de Cd en hojas, tallos y frutos de Cynara scolymus L. en el distrito Nueve de Julio (Tabla 2).…”
Section: Concentración De Cadmiounclassified
“…Machado (2016) reportó la concentración de Cd en hojas y frutos de alcachofa de cultivo comercial, en cuatro localidades de Uruguay, con promedios de 0,11 y 0,09 mg kg -1 , respectivamente, cumpliendo con los valores de 0,3 mg kg -1 Cd establecidos por el reglamento de MERCOSUR. Lizarazo et al (2020) evaluaron en Sibapé, Colombia, la contaminación de metales pesados en alcachofa, reportando para cadmio: 0,08; 0,16; 0,18; y 0,22 mg kg -1 en flores, raíces, tallos y hojas, respectivamente. El factor de transferencia para Cd, del suelo a la planta, fue de 78%.…”
Section: Introductionunclassified
“…UPL have been identified and occasionally linked to social factors such as industrialization in rural areas producing fruits or vegetables close to water basins, a potentially phytotoxic social setting [ 1 , 2 , 9 ]. Additionally, wastes from pharmaceutical products, pesticides, herbicides, organic fertilizers, and soil amendments are common vectors that, associated with soluble vehicles mobilized in river or wastewater, increase metal concentration in agricultural soils [ 5 , 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of UPL has been described in countries with different economic income levels, highlighting determining factors such as the use of wastewater for irrigating crops, mainly vegetables [ 1 , 9 12 ]; air pollution, transformed into atmospheric deposition with high nickel (Ni), lead (Pb), and cadmium (Cd) concentrations [ 11 , 12 ]; the proximity of crops to mining areas or industrial complexes, related to high copper (Cu) and arsenic (As) concentrations [ 7 , 11 , 12 ]; and the use of livestock manure as a crop fertilizer, associated with high mercury concentrations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of wastewater for irrigation has its own side effects, which include the bioaccumulation of toxic metals in crops and vegetables, resulting in public health risks. It has been reported that in high‐income countries, the management of wastewater is optimal compared with low‐income countries, where the problem is worsened by lack of fresh water for irrigation and no resources for wastewater treatment (Lizarazo et al., 2020). The cumulative effects and long‐term interactions and accumulation of the heavy metals in the soil contribute negatively to the environment, which includes animals and plants.…”
Section: Introductionmentioning
confidence: 99%